Synergy between protected conservation areas and community development : the case of Hluhluwe-Imfolozi Game Reserve KwaZulu-Natal Province South Africa - Stevens, Joseph Benjamin (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2018.